IMPLEMENTASI PERATURAN PRESIDEN NOMOR 12 TAHUN 2021 TENTANG PENGADAAN BARANG/JASA PEMERINTAH DI BIRO PENGADAAN BARANG DAN JASA PROVINSI RIAU TAHUN 2023 - Juliansyah, Khadhil Dhiyaulhaqi; ,, Wazni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Government procurement of goods and services remains one of the sectors most prone to corruption nationwide, despite continuous updates and adjustments to procurement policies in response to the development of digitalization. Therefore, this study aims to analyze the implementation process of Presidential Regulation No. 12 of 2021 and the challenges encountered in the procurement of goods and services by the Procurement Bureau of Riau Province. The analysis in this study refers to Charles O. Jones’ theory of implementation, which includes three key indicators: organization, interpretation, and application. This research employs a descriptive qualitative approach, using interview and documentation techniques for data collection. The findings reveal several issues, including the limited capacity of human resources within the Procurement Bureau of Riau Province, inadequate understanding of procurement processes among personnel, and resistance to regulatory changes among procurement stakeholders. Furthermore, the absence of updated Standard Operating Procedures (SOPs) related to procurement has hindered the synchronization between current regulations and practical implementation. To optimize the implementation of this policy, it is essential to strengthen the capacity of government officials, improve technological infrastructure, enhance coordination among stakeholders, and simplify the bureaucratic implementation of Presidential Regulation No. 12/2021. Keywords: Implementation, Procurement of Goods and Services, Good Governance.